Temperature regulates circadian rhythms of immune responses in red swamp crayfish Procambarus clarkii. Issue 2 (August 2015) - Dong, Chaohua; Bai, Suhua; Du, Liqiang
Abstract: As an ectothermic animal, crayfish immunity and their resistance to pathogen can be significantly affected by environmental factors such as light and temperature. It has been found for a long time that multiple immune parameters of animals and human are circadian-regulated by light-entrained circadian rhythm. Whether temperature also affects the immune rhythm of animals still remains unclear. In the present study, we investigated the effect of temperature cycles on the rhythm of crayfish immunity and their resistance. Survival experiments demonstrated that temperature cycles of 24 °C and 18 °C effectively entrained the circadian rhythm of crayfish resistance to Aeromonas hydrophila in constant dark. After being exposed to temperature cycles, the crayfish injected at different time points exhibited significant difference in resistance to A. hydrophila . Bacterial growth and total hemocyte count (THC) also showed circadian variation in crayfish subjected to temperature cycles, but phenoloxidase (PO) activity didn't show rhythmic change under the same conditions. Quantitative real-time PCR revealed that basal expression of crustin1 and astacidin in crayfish subjected to temperature cycles was circadian-rhythmic, but induced expression by A. hydrophila didn't show the same rhythm. In contrast, crayfish maintained at constant temperature showed completely arrhythmic in bacterial resistance, immune parameters mentioned above and the expression of antimicrobial peptides. The results present here collectively indicated that temperature cycles entrained circadian rhythm of some immune parameters and shaped crayfish resistance to bacteria. Highlights: Temperature cycles can entrain circadian rhythm of crayfish resistance to bacteria. Bacterial growth showed circadian variation in crayfish under temperature cycles. Circadian rhythm of THC can be entrained by temperature cycles in crayfish. The circadian expressed AMPs were observed in crayfish under temperature cycles. Phenoloxidase activity didn't show circadian variation under temperature cycles.